Theoretical and Practical Challenges of Integrating Electronic Evidence in Civil Adjudication - Adilova , Marjangul (INTERNATIONAL CONFERENCE ON SCIENCE, INNOVATION AND GLOBAL DEVELOPMENT, 2026)
The rapid migration of commercial and interpersonal interactions into digital ecosystems fundamentally disrupts traditional evidentiary paradigms in civil litigation. While statutory frameworks universally recognize the existence of digital artifacts, the procedural mechanisms for authenticating and admitting ephemeral binary data remain legally ambiguous. This investigation quantifies the admissibility rates and judicial evaluation patterns of electronic records within contemporary civil dispute resolution. Analyzing a stratified dataset of 450 recent civil court rulings where digital artifacts dictated the adjudicative outcome, the research identifies systemic discrepancies in forensic protocols. Empirical findings indicate a 42% rejection rate for uncertified electronic submissions, driven primarily by metadata spoliation and unverified chains of custody. Informal data streams, such as instant messaging logs, encountered severe judicial skepticism, facing a 58% dismissal rate due to inherent spoofing vulnerabilities. Conversely, the integration of cryptographic hashing techniques, specifically SHA-256 validation, reduced authenticity disputes to a mere 11%. The data exposes a critical lag between dynamic technological advancements and static civil procedure codes, which persistently apply analog "best evidence" rules to digital phenomena. To secure legal certainty, the study proposes a standardized algorithmic protocol for digital evidence authentication, establishing strict criteria for data integrity and replacing arbitrary judicial discretion with objective forensic verification.